Two-phase anaerobic treatment kinetics of palm oil wastes - Ng, W.J.; Wong, K.K.; Chin, K.K. (Elsevier, 1985)
A laboratory-scale two-phase anaerobic digestion system was used to treat a palm oil mill effluent (POME) containing around 63,000 mg l-1 COD. Phase separation was accomplished through control of the hydraulic retention times of two reactors operated in series. Acid and methane phase biokinetic coefficients were evaluated. Steady state parameters indicate good process stability with high gas yields.